2006
DOI: 10.1007/s10969-006-9008-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Vitamin B12 Biosynthetic Cobaltochelatase, CbiXS, from Archaeoglobus Fulgidus

Abstract: The Archaeoglobus fulgidus gene af0721 encodes CbiX(S), a small cobaltochelatase associated with the anaerobic biosynthesis of vitamin B12 (cobalamin). The protein was shown to have activity both in vivo and in vitro, catalyzing the insertion of Co2+ into sirohydrochlorin. The structure of CbiX(S) was determined in two different crystal forms and was shown to consist of a central mixed beta-sheet flanked by four alpha-helices, one of which originates in the C-terminus of a neighboring molecule. CbiX(S) is abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…The cocrystallization of Dv-CbiK P with cobalt was achieved by mixing 1.0 μL Dv-CbiK P with 1.8 μL reservoir solution and 0.2 μL 1.0 M cobalt chloride. Both the Se-CbiK and Af-CbiX S were purified and crystallized as previously described (5,6). The SHC complexes of Se-CbiK and Af-CbiX S were produced by anaerobic cocrystallization of equimolar quantities of CbiK and SHC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cocrystallization of Dv-CbiK P with cobalt was achieved by mixing 1.0 μL Dv-CbiK P with 1.8 μL reservoir solution and 0.2 μL 1.0 M cobalt chloride. Both the Se-CbiK and Af-CbiX S were purified and crystallized as previously described (5,6). The SHC complexes of Se-CbiK and Af-CbiX S were produced by anaerobic cocrystallization of equimolar quantities of CbiK and SHC.…”
Section: Methodsmentioning
confidence: 99%
“…The simplest of these enzymes is CbiX S , which has a subunit composed of around 130 amino acids (2). The structure of the Archaeoglobus fulgidus CbiX S (Af-CbiX S ) reveals that it forms a homodimer with a symmetrical active site and functional studies have shown that it is responsible for the chelation of Co 2þ into sirohydrochlorin (SHC) in the biosynthesis of cobalamin (5). These small forms of the enzyme are generally found in the Archaea and are thought to represent a primordial form of the protein.…”
mentioning
confidence: 99%
“…denitrificans, this ferrochelation is mediated by a CbiX-like protein (12), which is a member of the type II chelatase family (184) and displays significant structural similarity to the cobaltochelatases (185,186). Chromosomal inactivation of this cbiX gene in P.…”
Section: Color Changes Highlight the Pathwaymentioning
confidence: 99%
“…A similar situation arises for ribonucleotide reductase with a cobalamin-dependent, oxygen-independent type II form (E.C. Studies on the CbiX proteins [16] suggest the importance of conservation of the two histidine residues (the catalytic residues) as well as a glycine, proline and aspartic acid. A multiple sequence alignment of SCO01858, SCO1116 and several other CbiX proteins suggests that SCO1116 does not have the required patterns of conservation, although a global alignment of these two SCO proteins does indeed reveal global similarity.…”
Section: Cobalaminmentioning
confidence: 75%